Development of The STAD Cooperative Learning Model : Enhancing Mathematical Reasoning and Communication Skills in Higher Education - Nasution, Mariam; Rusdi, Rusdi; Nasution, Annisa (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop the STAD cooperative learning model specifically designed for mathematics education in a higher institution to impact students’ reasoning and communication skills. The study holds significance in its comprehensive analysis, encompassing (1) Plomp Stage 1 Schematic: Preliminary Study; (2) Plomp Stage 2 Schematic: Development Study; and (3) Plomp Stage 3 Schematic: Assessment Study of the developed STAD learning model. The method employed was Research and Development (R&D), utilizing questionnaires, tests, and observations as data collection techniques. The present research involved students at a university in Padangsidimpuan, North Sumatra, Indonesia. The analysis techniques used were inferential statistics and descriptive statistics. The findings indicated that: (1) The preliminary study of the model was conducted based on needs analysis incorporating the curriculum, student, and learning materials; (2) The modelâ€™s development study, encompassing six phases, yielded a significant validation result of 3.84, categorized as â€˜Goodâ€™; (3) The assessment study, in terms of practicality, obtained a score of 4.60 (considered â€˜Goodâ€™), and effectiveness demonstrated positive significance in affecting students’ reasoning and communication skills. The overarching conclusion drawn is that the research and development of the STAD learning model revealed significant positive impacts on students’ reasoning and communication skills.